EVALUASI KELAYAKAN BISNIS TELUR ASIN PADA UD. KENANGA DI KELURAHAN AMPENAN SELATAN KECAMATAN AMPENAN KOTA MATARAM - I GUSTI AGUNG DIDIT EKA PERMADI; ELOK AULIA RIZQI MALIGAN; I DEWA GEDE SUARTHA (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
The purpose of this study was to analyze the feasibility of salted egg business/business at UD. Kenanga, South Ampenan Village, Ampenan District, Mataram City. This research is applied research. The data collection method used in this study is the case method or often called a case study. Based on the results and discussion, it can be concluded that the salted egg agro-industry business/business UD. Kenanga is profitable and feasible to be cultivated because it has a B/C Ratio value of 0.54 and BEP (Q) is obtained as many as 217 items, while BEP (Rp) is obtained at Rp. 850,902.5.